2004
DOI: 10.1177/147323000403200217
|View full text |Cite
|
Sign up to set email alerts
|

A New Tactile Skin Sensor for Measuring Skin Hardness in Patients with Systemic Sclerosis and Autoimmune Raynaud's Phenomenon

Abstract: We used a new tactile sensor to measure the elastic properties of skin in patients with systemic sclerosis or Raynaud's phenomenon. The sensor consists of a piezoelectric vibrator with vibration pickup to measure frequency changes when the sensor is placed on the skin. The mean frequency change at the skin surface of the proximal third phalanx in patients with systemic sclerosis was significantly lower than in age-and sexmatched controls. The results in systemic sclerosis patients were statistically correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In addition, the system has been applied to the measurement of the hardness of skin, muscle, and cartilage in laboratory experiments and even in clinical evaluations. [16][17][18][19] Because the hardness of the distraction callus we measured was between the soft tissue and cartilage, we thought that this technique was valid in our study. The biosensor has a natural oscillating piezoelectric element and detects the change in frequency produced by the contact of the sensor with the tenting material as hardness.…”
Section: Distraction-callus Hardness Measurementmentioning
confidence: 92%
“…In addition, the system has been applied to the measurement of the hardness of skin, muscle, and cartilage in laboratory experiments and even in clinical evaluations. [16][17][18][19] Because the hardness of the distraction callus we measured was between the soft tissue and cartilage, we thought that this technique was valid in our study. The biosensor has a natural oscillating piezoelectric element and detects the change in frequency produced by the contact of the sensor with the tenting material as hardness.…”
Section: Distraction-callus Hardness Measurementmentioning
confidence: 92%
“…Hence, the restoration of reaction force feedback and tactile information is needed for safer and more accurate robotic surgery. In order to realize the haptic feedback, many types of haptic master and tactile device have been proposed [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. However, RMIS systems with reaction force or tactile feedback showed limited performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on tactile devices that can be integrated with haptic masters have been performed for robot surgery [16,17]. However, these studies have also identified difficulty in realizing the various sensations of human organs by touching sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[171013] A tactile resonance sensor developed by Lindahl and Omata has yielded results similar to those achieved by palpation[11] and has already been used in studies assessing the stiffness of soft tissues. [31416] The stiffness of living tissue can be quantitatively derived from elasticity and viscosity in mechanical analysis, and hence measurement of elasticity with a tactile resonance sensor placed on an external decompression may be an objective measure of brain stiffness. Overall brain stiffness is derived from the stiffness of the pia-arachnoid, gray matter, white matter, cerebrospinal fluid (CSF), and cerebral blood vessels.…”
Section: Introductionmentioning
confidence: 99%